Enhancing control of multidrug-resistant plasmid and its host community with a prolonged thermophilic phase during composting - Shen, Lei; Qiu, Tianlei; Guo, Yajie; Gao, Min; Gao, Haoze; Zhao, Guozhu; Wang, Xuming (Frontiers in Microbiology, 2022)
The plasmid-mediated horizontal transfer of antibiotic resistance genes (ARGs) among bacteria facilitates the evolution and dissemination of antibiotic resistance. Broad-host-range plasmids can be transferred to different bacterial hosts in soil, plant rhizospheres, and wastewater treatment plants. Although composting is an effective way to convert organic waste into fertilizer and reduce some ARGs, few studies have focused on its effects on the spread of ARG-carrying plasmids and their bacterial host communities during composting. In this study, a fluorescently labeled Pseudomonas putida (P. putida) harboring a broad-host-range plasmid RP4 carrying three ARGs was inoculated into a raw material microcosm and composted with different durations of the thermophilic phase. The fate of the donor and RP4 in composting were investigated. The prolonged thermophilic composting removed 95.1% of dsRed and 98.0% of gfp, and it inhibited the rebound of P. putida and RP4 during the maturation phase. The spread potential of RP4 decreased from 10-4 to 10-6 transconjugants per recipient after composting. In addition, we sorted and analyzed the composition of RP4 recipient bacteria using fluorescence-activated cell sorting combined with 16S rRNA gene amplicon sequencing. The recipient bacteria of RP4 belonged to eight phyla, and Firmicutes, accounting for 75.3–90.1%, was the dominant phylum in the transconjugants. The diversity and richness of the RP4 recipient community were significantly reduced by prolonged thermophilic periods. Overall, these findings provide new insights for assessing the contribution of composting in mitigating the dissemination of plasmid-mediated ARGs, and the prolonged thermophilic phase of composting can limit the transfer of multidrug-resistant plasmids.